Effective Resolution of Ethical Dilemmas in Social Enterprise Organizations: A Moral Philosophy and Public Management Approach. (2nd January 2020) - Heckler, Nuri; Ronquillo, John C.
Abstract : Public service ethics can provide social enterprise organizations (SEOs) with a means of complementing business ethics. Many public service ethics scholars recognize that internal and external ethics sources combine to create stronger ethical guidelines for public servants. This study argues that the classical deontological and teleological debate can provide a useful understanding of ethics as well. Combining the internal/external spectrum with the deontological/teleological spectrum of ethical sources to create four categories for understanding sources of ethical resolutions, this study uses ethnomethodology to find that SEO managers expend fewer resources resolving ethical dilemmas when they reference ethical sources from multiple categories. The study finds that SEO managers who have access to multiple sources of ethics develop more confidence in potential resolutions, and are thus able to dedicate more resources to achieving mission-oriented outcomes.